VIS COGITATIVA JAKO PODMIOTOWA RACJA POZNANIA ISTNIENIA JEDNOSTKOWYCH RZECZY - Sulenta, Paulina (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The analyses made in the article belong to research on the problematic of man’s ability to acquire knowledge about what is individual and concrete. The purpose of these reflections is to present the subjective justification for the possibility of the apprehension of the individual thing; this is reduced to the indication of an appropriate faculty and subject in man. In classical metaphysics the particular reason, which is also called the cogitative faculty or power (vis cogitativa), is usually regarded as this reason. The author presents the interpretation of the cogitative faculty that M.A. Krąpiec made in the work Realizm ludzkiego poznania [The realism of human knowledge]. In the first she concentrates on the two orders of knowledge composed of the essence and existence of being. Despite the appearance that the process of knowledge moves on two different tracks, one observes close cooperation in the action of the sensory and intellectual powers; this cooperation results in a holistic perspective of an existing individual. In the second part, the author describes what the vis cogitativa is and how it acts, and compares it with the faculty of instincts in animals (vis aestimativa). In the functioning of the human and the animal senses there is no difference with regard to the change that occurs in the organ and faculty under the influence of external stimuli. However, there is a difference in the representation of the thing that takes shape in those subjects. The specific character of the function of the particular reason is expressed primarily in the synthesis of the elements of sensory and intellectual knowledge; by that synthesis it becomes possible to read and interpret the existing individual as a realization of a certain general nature, that is, as a subject that exists in itself. Thereby also the cogitative faculty, which is the place where existential judgements concerning material things are made, is presented as the main factor that provides a foundation from the side of the subject for cognitive realism.